APLIKASI CONSTRUCT 2 UNTUK MERANCANG GAME “PETUALANGAN SI BELONG” - Wijaya, Benny Tri; Noor Santi, Rina Candra (Information Technology and Telematics, 2018)
Abstract Culture and art must be owned by every region in Indonesia. One area that has an abundant variety of cultures and arts is Jepara. Today's children are starting to forget and more children today choose to play smartphones. Therefore, this study aims to find out how to create a game application "Belong Adventure" using construct 2 with an easy-to-use design and can be an educational medium for children. This game starts from needs analysis, design, coding, testing, maintenance. The game "Belong Adventure" uses collisions detection method, the game model is presented in the form of large-eyed small children in Jepara called Belong as the main character and there are 3 levels of adventure genre, at level 1 there is a mini game guessing images, at level 2 There is a mini choice quiz game and on level 3 mini puzzle games. Tests were carried out on 3 android devices with different specifications. The results showed the game "Adventure of the Belong" can be run on an Android device easily.